Feminism And Marginal Sectors: Achievements And Setbacks In A Difficult Dialog - Juliano D. (Cadernos pagu, 2016)
The feminist movement has given voice to the demands of women and assured their conquests and demands. But not all groups of women have been equally recognized. Groups with greater social marginalization have the greatest difficulties inserting their demands within the hegemonic lines of feminism. There are currently polemics about how to approach themes such as sexual work and female crime. © 2016, Universidade Estadual de Campinas UNICAMP. All rights reserved.20164